2017
DOI: 10.1038/srep40214
|View full text |Cite
|
Sign up to set email alerts
|

Aminophylline suppresses stress-induced visceral hypersensitivity and defecation in irritable bowel syndrome

Abstract: Pharmacological therapy for irritable bowel syndrome (IBS) has not been established. In order to find candidate drugs for IBS with diarrhea (IBS-D), we screened a compound library of drugs clinically used for their ability to prevent stress-induced defecation and visceral hypersensitivity in rats. We selected the bronchodilator aminophylline from this library. Using a specific inhibitor for each subtype of adenosine receptors (ARs) and phosphodiesterases (PDEs), we found that both A2BARs and PDE4 are probably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Previously, in a phenotypic screening, we identified aminophylline as a drug that suppressed visceral sensitivity response to repeated CRD. Aminophylline suppressed stress‐induced visceral hypersensitivity by inhibiting adenosine A 2 receptors (Asano et al, ). In the same screen, chlorpromazine showed similar effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, in a phenotypic screening, we identified aminophylline as a drug that suppressed visceral sensitivity response to repeated CRD. Aminophylline suppressed stress‐induced visceral hypersensitivity by inhibiting adenosine A 2 receptors (Asano et al, ). In the same screen, chlorpromazine showed similar effects.…”
Section: Discussionmentioning
confidence: 99%
“…VMR to CRD was monitored as described previously (Asano et al, ). Briefly, rats were deeply anaesthetized with an intraperitoneal injection of mixture of medetomidine chloride (0.5 mg·kg −1 ), midazolam (2.5 mg·kg −1 ) and butorphanol tartrate (2.5 mg·kg −1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine's role in diverse enteric functions and disease processes are extensively reviewed elsewhere (6,7). Recent data show that, in rat models of IBS (based on stress such as maternal separation or wraprestraint stress), the A 2B receptor antagonist aminophylline reduced visceral pain as well as colonic propulsion (9).…”
Section: Adenosine A2b Receptor Agonistmentioning
confidence: 99%
“…Recently, we reported that blockade of the A 2B receptor could be beneficial for diarrhoea-predominant IBS 8 . Inhibition of the receptor by pharmacological agents ameliorated colonic hypersensitivity and stress-induced defecation in rodent models of IBS.…”
mentioning
confidence: 99%